Animals and the Problem of Evil in Recent Theodicies - Maller, Mark (Sophia, 2009)
This essay critically evaluates the theodicies of John Hick, Richard Swinburne and process theism regarding animal suffering and evils. Their positions on animals are found to be flawed and/or inadequate because they cannot explain the mass suffering and unnecessary deaths to animals throughout time. I also offer a positive contribution. That is, God’s putative love for all humans and animals does not entail that he loves every single human and animal. It is very possible that God treats humans and animals similarly in regard to evils. This theory partly explains human tragedies such as the Holocaust and much unnecessary animal and human suffering.